The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1921
DOI: 10.5962/bhl.title.34545
|View full text |Cite
|
Sign up to set email alerts
|

A to z of pigeons, fancy and utility, with latest standards, by J. W. Williamson.

Abstract: English Carriers 13 dred-fold to do so. This is why I believe in flies not over six and one half feet high, low alighting boards, and the alleyways in front of the houses instead of the rear, so as to be always near the birds. Fancy Breeds Cultivate the spirit of love toward them, and you will be paid for all such trouble, no ntatter how many birds you have. Two thousand can be kept tame and quiet as well as one hundred and they will work better. Other Habits-The coo of some birds is different from others. 1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(79 citation statements)
references
References 0 publications
8
71
0
Order By: Relevance
“…This is not the first time that a heterogeneity of different creatine kinases has been found. It has been described in several reports on creatine kinases of various vertebrate species including human [28-301, rabbit [31,32] chick [33] and also trout [34,35]. As many separation techniques as studies have been carried out (starch gels, urea-starch gels, agarose gels, sodium dodecylsulphate/polyacrylamide gels and preparative isoelectric focusing) so that it is difficult to compare the different results with ours.…”
Section: Discussionmentioning
confidence: 90%
“…This is not the first time that a heterogeneity of different creatine kinases has been found. It has been described in several reports on creatine kinases of various vertebrate species including human [28-301, rabbit [31,32] chick [33] and also trout [34,35]. As many separation techniques as studies have been carried out (starch gels, urea-starch gels, agarose gels, sodium dodecylsulphate/polyacrylamide gels and preparative isoelectric focusing) so that it is difficult to compare the different results with ours.…”
Section: Discussionmentioning
confidence: 90%
“…APC within the eye are bathed in an environment rich in TGF-P2 [8, 421. Intraocular injection of antigen mobilizes these cells, inducing them to migrate through the trabecular meshwork into the blood, whence they are carried to the spleen [12,[21][22][23]. In the splenic milieu, they present eye-derived antigens to novel populations of specific T and B lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…While the immunosuppressive properties of transforming growth factor-p (TGF-8) have usually been examined with respect to the effects of this cytokine on T cells [l-51, there is good evidence to suggest that TGF-8 may suppress T cell activation indirectly, that is, by a primary action on antigen-presenting cells (APC; [6]). This distinction takes on special meaning in certain organs of the body, such as the eye, the brain, and the fetavplacental unit, where immune privilege has been documented, where the local fluids (aqueous humor, cerebrospinal fluid, amniotic fluid) contain significant amounts of TGF-P [7-lo], and where indigenous bone marrow-derived dendritic cells and macrophages reside [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Williamson et al [1] found contrast sensitivity to be within the normal range with polymethylmethacrylate (PMMA) IOLs. No significant difference was found between the contrast sensitivity with PMMA and silicone IOLs [2] or between PMMA and hy drogel IOLs [3], Bifocal IOLs have shown decreased con trast sensitivity values for intermediate spatial frequencies compared to monofocal IOLs [4], No studies could be found o f contrast sensitivity with silicone IOLs compared to normal eyes.…”
Section: Introductionmentioning
confidence: 99%